Pengembangan Bahan Ajar Berbasis Deep Learning Materi Tradisi di Lingkungan Keluarga dan Masyarakat Kelas III SDN Percobaan Palangka Raya - Muhammad Syabrina; Elsa Aulia Rahmadani; Elsa Rabiatul Adawiyah; Meilin Adetia; Adelia Meilestari (JURNAL ILMIAH NUSANTARA, 2026)
In the era of the industrial revolution 4.0, teaching materials need to be adapted to technological developments so that students can be interested. The type of teaching material that can attract students' interest is teaching materials in the form of interactive media. This study aims to develop digital teaching materials in the form of interactive learning media that can be used by students in grade III in science learning. This study follows the ADDIE model with five stages, namely analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, documentation, and questionnaires. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was very appropriate, with a percentage score reaching 92,71% including the "Very Appropriate" Qualification according to design experts 99,07%, teacher assessment of 98,53%, field trial results 86,34%, T-Test Results 0.00 that the teaching materials were very significant in improving learning outcomes, and N-gain Analysis of 0,78 with high criteria. While the effectiveness of the teaching materials was 78.13 with the category of effective use in learning. The conclusion of the research on the development of teaching materials can improve student learning outcomes.